1993
DOI: 10.1507/endocrj.40.473
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in isolated Adrenocorticotropic Hormone (ACTH) Deficiency: Case Report and Literature Review.

Abstract: Abstract. A case of isolated ACTH deficiency accompanying transient primary hypothyroidism was reported along with a review of literature on isolated ACTH deficiency in Japan with special reference to its association with thyroid function. Our case, a 56-year-old woman, developed somnolence and hypoglycemia due to isolated ACTH deficiency. She also had the features of hypothyroidism, namely mounding phenomenon, muscle rigidity, increased plasma myogenic enzymes and cold intolerance. Both free T3 and free T4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Autoimmune thyroiditis is fairly commonin Japanese, and about 10-20% of the female population and about 5%of the male are positive for the anti-microsomal and anti-thyroglobulin antibody (19). Solely 3% of the patients with ACTHdeficiency represent hyperthyroidism, as we have shownpreviously (18). These results may not support the concept that the prevalence of autoimmunethyroid disease is significantly higher in patients with secondary and tertiary hypocortisolism than in the Japanese general population.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Autoimmune thyroiditis is fairly commonin Japanese, and about 10-20% of the female population and about 5%of the male are positive for the anti-microsomal and anti-thyroglobulin antibody (19). Solely 3% of the patients with ACTHdeficiency represent hyperthyroidism, as we have shownpreviously (18). These results may not support the concept that the prevalence of autoimmunethyroid disease is significantly higher in patients with secondary and tertiary hypocortisolism than in the Japanese general population.…”
Section: Discussioncontrasting
confidence: 66%
“…This would also be the case for the results of the LH-RHtest. As we have shown previously, glucocorticoid affects the TSH-thyroid axis, which is more easily seen in patients with intrinsic thyroid disease (18). Physiological concentrations of glucocorticoid mayhave a suppressive effect on the manifestation of autoimmune thyroid disease.…”
Section: Discussionmentioning
confidence: 62%
“…The present patient also had Hashimoto's thyroiditis, as indicated by the diffuse goiter and positive tests for anti-thyroid antibodies. Both Murakami et al [10] and Hashimoto [6] have reported literature reviews about IAD associated with thyroid disorders in Japan. According to Murakami et al's review of 103 cases, 13 cases (12.6%) were positive for anti-thyroid antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In patient 1, the pituitary tumor has not been examined histologically and has not changed in size so far, so it is necessary to follow up the tumor clinically and radiologically to establish the exact diagnosis. Isolated ACTHdeficiency is sometimes accompanied by various neuromusculardisturbances such as muscleatrophy (10), weakness (10), myalgia (ll, 12), cramps (ll, 12), contracture (10, 12, 13), rigidity (14,15), and peripheral neuropathy (12,15), but little attention has been paid to NMS-like symptoms. In the literature, there are 3 patients with isolated ACTH deficiency whopresented with NMS-like symptoms.…”
Section: Discussionmentioning
confidence: 99%